2006
DOI: 10.1590/s1517-83822006000200014
|View full text |Cite
|
Sign up to set email alerts
|

Gordonia polyisoprenivorans from groundwater contaminated with landfill leachate in a subtropical area: characterization of the isolate and exopolysaccharide production

Abstract: A strain of Gordonia sp. (strain Lc), from landfill leachate-contaminated groundwater was characterized by polyphasic taxonomy and studied for exopolysaccharide (EPS) production. The cells were Gram-positive, catalase-positive, oxidase-negative and non-motile. The organism grew both aerobically and, in anoxic environment, in the presence of NaNO3. Rods occured singly, in pairs or in a typical coryneform V-shaped. The organism had morphological, physiological and chemical properties consistent with its assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Bacteria in the genus Gordonia have been isolated from various petroleum hydrocarbon-contaminated sites, including oily seawater (Arenskötter et al, 2004;Brito et al, 2006;Quatrini et al, 2008;Shen et al, 2008). Earlier reports demonstrated that Gordonia persist in severe conditions and possess special cellular physiology, including high cell surface hydrophobicity, emulsifi cation activity and EPS synthesis, to enhance hydrophobic substrate uptake (Arenskötter et al, 2004;Franzetti et al, 2009;Fusconi et al, 2006Fusconi et al, , 2010. Thus, it is possible to use Gordonia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria in the genus Gordonia have been isolated from various petroleum hydrocarbon-contaminated sites, including oily seawater (Arenskötter et al, 2004;Brito et al, 2006;Quatrini et al, 2008;Shen et al, 2008). Earlier reports demonstrated that Gordonia persist in severe conditions and possess special cellular physiology, including high cell surface hydrophobicity, emulsifi cation activity and EPS synthesis, to enhance hydrophobic substrate uptake (Arenskötter et al, 2004;Franzetti et al, 2009;Fusconi et al, 2006Fusconi et al, , 2010. Thus, it is possible to use Gordonia sp.…”
Section: Discussionmentioning
confidence: 99%
“…It was first isolated from automobile tyres and is one of the few available latex degrading microbes (Ding et al, 2017). In addition, G. polyisoprenivorans converts sugars to extracellular polysaccharides, which is responsible for the formation of biofilms (Fusconi et al, 2006). One of the few chemoheterotrophs enriched on biofilms were Sphingobium aminese, which was present specifically on EB and plank samples (Fig.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…The amount of total EPS produced by G. polyisoprenivorans CCT 7137 was higher than that observed by Fusconi et al (2006) in the culture of G. polyisoprenivorans CCT 7277 in E medium containing glucose. The latter produced a maximum of 126.17 g L -1 during the stationary phase.…”
Section: Resultsmentioning
confidence: 55%